Stress Controls of Monogenetic Volcanism: A Review - Martí, Joan; López, Carmen; Bartolini, Stefania; Becerril, Laura; Geyer, Adelina (Frontiers in Earth Science, 2016)
The factors controlling the preparation of volcanic eruptions in monogenetic fields are still poorly understood. The fact that in monogenetic volcanism each eruption has a different vent suggests that volcanic susceptibility has a high degree of randomness, so that accurate forecasting is subjected to a very high uncertainty. Recent studies on monogenetic volcanism reveal how sensitive magma migration is to the existence of changes in the stress field caused by regional and/or local tectonics or rheological contrasts (stratigraphic discontinuities). These stress variations may induce changes in the pattern of further movements of magma, thus conditioning the location of future eruptions. This implies that a precise knowledge of the stress configuration and distribution of rheological and structural discontinuities at crustal level of such volcanic systems would aid in forecasting monogenetic volcanism. This contribution reviews several basic concepts relative to the stress controls in monogenetic volcanic fields, and uses this information to explain how magma migrates inside such volcanic systems and how it prepares to trigger a new eruption.